ANALISIS KEARIFAN LOKAL TANAMAN KARET DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Faisal Azmi; Eri Sayamar; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to identify local wisdom is ever existed  rubber plant (from past done but did not do it present), which is still carried out and the rubber farmers who were past and the present  do,  and which were not past done but present do of rubber farmers. This research  uses survey and SnowBall Sampling method in finding the proper respondent to obtain the 15 respondents consisting of 1) Farmers Rubber, 2) Ninik Mamak, 3) Religious Leaders, 4) Apparatus Village, 5) members of farmer groups, 6) Patron(Induk Semang). Methods interviews were conducted to obtain information about local wisdom rubber plants. Descriptive and qualitative analysis in preparing this research. Criteria that respondents who sought rubber farmers who have long experience and the cultivation of local wisdom to know the rubber plant. The results showed that local wisdom of rubber plant by the farmers in cultivation in 1) Land Clearing  that are amounted 21 local wisdom, 2) Nurseries amounted 5 local wisdom 3) Planting amounted 9 local wisdom,  4) The period before production amounted 2 local wisdom,  5) Maintenance amounted 18 local wisdom and 6) Rejuvenation amounted  4 local wisdom, 6) Rubber tapping amounted 15 local wisdom,  7) Processed Materials Rubber amounted 4 local wisdom,  8) Marketing amounted  4 local wisdom. The total local wisdom of rubber plant that 82 local wisdom. Application of local wisdom rubber plant is dominated by the activity pattern of human behavior, actions / activities that reflect the daily life of the local community and religion.   Keywords: Local Wisdom, Rubber Plant, Rubber Farmers, Past, Present